Whole exome sequencing identifies recessive PKHD1 mutations in a Chinese twin family with Caroli disease. - Xiwei Hao; Shiguo Liu; Qian Dong; Hong Zhang; Jing Zhao; Lin Su (PLoS ONE)
Background Mutations in PKHD1 cause autosomal recessive Caroli disease, which is a rare congenital disorder involving cystic dilatation of the intrahepatic bile ducts. However, the mutational spectrum of PKHD1 and the phenotype-genotype correlations have not yet been fully established. Methods Whole exome sequencing (WES) was performed on one twin sample with Caroli disease from a Chinese family from Shandong province. Routine Sanger sequencing was used to validate the WES and to carry out segregation studies. We also described the PKHD1 mutation associated with the genotype-phenotype of this twin. Results A combination of WES and Sanger sequencing revealed the genetic defect to be a novel compound heterozygous genotype in PKHD1, including the missense mutation c.2507 T>C, predicted to cause a valine to alanine substitution at codon 836 (c.2507T>C, p.Val836Ala), and the nonsense mutation c.2341C>T, which is predicted to result in an arginine to stop codon at codon 781 (c.2341C>T, p.Arg781*). This compound heterozygous genotype co-segregates with the Caroli disease-affected pedigree members, but is absent in 200 normal chromosomes. Conclusions Our findings indicate exome sequencing can be useful in the diagnosis of Caroli disease patients and associate a compound heterozygous genotype in PKHD1 with Caroli disease, which further increases our understanding of the mutation spectrum of PKHD1 in association with Caroli disease.